Throwing performance after high-velocity low-amplitude thrust manipulation at the cervicothoracic and thoracolumbar junction in elite female water polo players: a randomized blind cross-over study - van der Kolk, H. K.; Scafoglieri, A. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: The effect of high-velocity low-amplitude (HVLA) thrust manipulation at the cervicothoracic and thoracolumbar junction in healthy elite female water polo players on throwing performance is unknown. METHODS: Ten healthy members of the Dutch National female water polo team participated in this randomized blind cross-over study. All received a HVLA manipulation and a sham manipulation at the cervicothoracic and thoracolumbar junction. Hereafter maximum throwing speed, range of motion and isometric strength were measured at 1 hour, 48 hours and 4 weeks follow-up. RESULTS: No significant differences in maximum throwing speed was found between HVLA and sham manipulation. In the non-dominant shoulder external rotation increased significantly (5.3±6.7°) 48 hours after sham manipulation, this effect was not considered clinically significant and diminished after four weeks. CONCLUSIONS: Our results suggest that HVLA and sham manipulation had no effect on shot velocity or shoulder mobility and the same effect on shoulder strength in healthy elite female water polo players. The common use of cervicothoracic and thoracolumbar HVLA manipulation for improving performance in this specific group of athletes is therefore questionable.